Mathematical Communication Skills in Terms of Self-Confidence of Grade XI Students at SMA Negeri 3 Palangka Raya - Damayanti, Heny; Winata, Rahmat; Friantini, Rizki Nurhana (JURNAL PENDIDIKAN, 2025)
This study aims to determine the mathematical communication ability in terms of students self- confidence in solving problems related to statistical material. The type of research used is qualitative descriptive research. This research was conducted in the even semester of the 2024/2025 academic year. The subjects in this study were 25 students, taken 3 students with each student with high, medium, and low self-confidence. The data collection technique used 3 essay test questions on statistical material, a self-confidence questionnaire, and interviews. The data obtained were then analyzed based on indicators of mathematical communication ability, namely, presenting mathematical symbols, making mathematical models, and writing. The results of the study showed that students with high self-confidence had high mathematical communication skills and were able to meet all indicators of mathematical communication ability. Students with medium and low self-confidence had medium mathematical communication skills and met two indicators of mathematical communication ability. Students with medium and low self-confidence were only able to meet two indicators, namely presenting mathematical symbols and writing. Therefore, teachers are expected to be able to improve students' mathematical communication skills by increasing joint discussion activities, presentations, question and answer sessions between teachers and students and students with students, as well as providing students with lots of practice questions so that students' self-confidence also increases.